THE REPRESENTATION OF ENGLISH FOR MEDICAL PURPOSES IN INDONESIAN VOCATIONAL LANGUAGE POLICY: A CRITICAL DISCOURSE ANALYSIS PERSPECTIVE - Sukisno; Suseno, Muchlas; Lustyantie, Ninuk (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the representation of EMP in key Indonesian vocational English language policy documents. Despite the increasing demand for clinical communication skills among healthcare professionals in the globalized medical landscape, EMP remains largely absent in national curriculum standards and policy guidelines. Using a qualitative approach based on CDA, particularly Fairclough’s three-dimensional model and Wodak’s Discourse-Historical Approach, this research analyzes how policy texts construct, silence, or marginalize domain-specific language needs, especially in the medical sector. The data consist of four national policy documents published between 2010 and 2024: Permendiknas No. 47/2010, Perpres No. 8/2012 on the National Qualifications Framework (KKNI), ESP Graduate Competency Standards, and the 2020 English training curriculum. Findings show that English is predominantly represented as a tool for economic mobility and global competitiveness. At the same time, medical communication needs are excluded from both the textual and ideological layers of policy. The absence of EMP is not incidental but reveals an underlying economistic discourse that privileges business-oriented English over ethical and human-centered communication. This study contributes to applied linguistics and language policy literature by highlighting the ideological bias in vocational ESP policy and advocating for the inclusion of EMP as a recognized curricular domain. Implications include curriculum reform, the need for cross-sector collaboration, and the development of a national EMP framework aligned with the competencies required in healthcare professions.